Critical Discourse Analysis in the Classroom: A Critical Language Awareness on Early Children’s Critical Thinking - Tutiariani Nasution; Desi Afrianti; Tukiyo Tukiyo; Sulistyani Sulistyani; Herman Herman (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
By using CDA as a tool in the classroom, this study visually and verbally analyses the children's growth. This is based on the understanding that learning is not content-oriented, but rather about the learning process of knowledge gained. Students who can think well will be successful in life. Therefore, this study aims to determine the app implementing critical discourse analysis on early children's development in the classroom. The method used is a qualitative approach with a literature review using sources from the internet, books, and related research outputs. Based on the study's findings, the critical thinking structure is explicit to make clear what is to be learned in order to facilitate writing skills, systematic to provide a consistent framework for focusing on both language and context, needs-based to ensure that course objectives and content are derived from students' needs, supportive to give teachers a central role in scaffolding students' learning and creativity, and empowering to give access to the pattern and possibilities.